Sexually Transmitted Diseases in Africa - De Schryver, Antoon; Meheus, André (Afrika Focus, 1990)
Sexually transmitted diseases (STD) are defined as a group of communicable diseases which have in common that they are transmitted predominantly by sexual contact. The number of agents now known to be sexually transmitted include some 20 pathogens. Some of these agents (such as Chlamydia trachomatis, herpes simplex virus, human papilloma virus, hepatitis B. virus, human immunodeficiency virus) tend to replace the classical "venereal diseases" both in importance and frequency as these agents are often more difficult to detect, treat, and control. Sexually transmitted diseases are a major public health problem in most African countries on account of their frequency, their associated morbidity and mortality, their impact on maternal and infant health, as well as their economic costs in terms of health expenditure and lost productivity, and, last but not least, because of their social consequences. Recent epidemiological studies using sophisticated diagnostic technologies greatly extend our knowledge on the true spectrum of complications and sequelae associated with these infections. Nongonococcal urethritis - caused to 40% by Chlamydia trachomatis - and gonococcal infections are together the most frequent sexually transmitted diseases. The increasing importance of chlamydial infections, in contrast to a gradual decrease of gonococcal infections, is related to the fact that these infections Sexually transmitted diseases (STD) are defined as a group of communica- ble diseases which have in common that they are transmitted predominantly by sexual contact. The number of agents now known to be sexually trans- mitted include some 20 pathogens. Some of these agents (such as Chlamydia trachomatis, herpes simplex virus, human papilloma virus, hepatitis Br virus, human immunodeficiency virus) tend to replace the classical "vene- real diseases" both in importance and frequency as these agents are often more difficult to detect, treat, and control. Sexually transmitted diseases are a major public health problem in most African countries on account of their frequency, their associated morbidity and mortality, their impact on maternal and infant health, as well as their economic costs in terms of health expenditure and lost productivity, and, last but not least, because of their social consequences. Recent epidemio- logical studies using sophisticated diagnostic technologies greatly extend our knowledge on the true spectrum of complications and sequelae asso- ciated with these infections. Nongonococcal urethritis - caused to 40% by Chlamydia trachomatis - and gonococcal infections are together the most frequent sexually transmitted diseases. The increasing importance of chlamydial infections, in contrast to a gradual decrease of gonococcal infections, is related to thefact that these infections frequently cause asymptomatic or mild disease and do not motivate patients to seek medical care, resulting in an extended period of infectivity and high risk of developing complications. Untreated gonorrhoea and chlamydial infections are the most common causes of epididymitis in males under the age of 35 years and may lead to decreased fertility. In some parts of sub-saharan Africa where urethritis often goes untreated, epididymitis is the leading course of male infertility. Also urethral strictures still from a large part of urogenital practice in some African countries. An estimated 8-16% of women with untreated endocervical gonococcal or chlamydial infections will develop acute salpingitis following an ascending spread of these pathogens. After one episode of acute salpingitis approximately 10% of women may become infertile due to complete tubal occlusion. Similarly, the risk for women to develop an ectopic pregnancy after salpingitis is 6-10 times greater than in controls. Ectopic pregnancies in areas with insufficient health services carry a high mortality risk. Maternal infections with STD may not only have adverse effects on pregnancy outcome but may cause serious morbidity and mortality in the newborn (e.g. congenital syphilis, ophthalmia neonatorum, herpes simplex virus infection of the neonate, chlamydial pneumonia, congenital HIV infection). AIDS is an example "par excellence" of a sexually transmitted disease of public health importance requiring extensive clinical services and posing enormous financial and social problems for the individual and the society at large. AIDS and the other viral STD have greatly increased the interest in primary prevention strategies such as health education and behavioral modification, for the control of sexually transmitted diseases. KEYWORDS: chancroid, chlamydia, gonorrhoea, HIV, infertility, sexually transmitted diseases, surveillance